A tissue-specific role for Nlrp3 in tubular epithelial repair after renal ischemia/reperfusion - Bakker, Pieter J; Butter, Loes M; Claessen, Nike; Teske, Gwendoline J D; Sutterwala, Fayyaz S; Florquin, Sandrine; Leemans, Jaklien C (The American journal of pathology, 2014)
Ischemia/reperfusion injury is a major cause of acute kidney injury. Improving renal repair would represent a therapeutic strategy to prevent renal dysfunction. The innate immune receptor Nlrp3 is involved in tissue injury, inflammation, and fibrosis; however, its role in repair after ischemia/reperfusion is unknown. We address the role of Nlrp3 in the repair phase of renal ischemia/reperfusion and investigate the relative contribution of leukocyte- versus renal-associated Nlrp3 by studying bone marrow chimeric mice. We found that Nlrp3 expression was most profound during the repair phase. Although Nlrp3 expression was primarily expressed by leukocytes, both leukocyte- and renal-associated Nlrp3 was detrimental to renal function after ischemia/reperfusion. The Nlrp3-dependent cytokine IL-1β remained unchanged in kidneys of all mice. Leukocyte-associated Nlrp3 negatively affected tubular apoptosis in mice that lacked Nlrp3 expression on leukocytes, which correlated with reduced macrophage influx. Nlrp3-deficient (Nlrp3KO) mice with wild-type bone marrow showed an improved repair response, as seen by a profound increase in proliferating tubular epithelium, which coincided with increased hepatocyte growth factor expression. In addition, Nlrp3KO tubular epithelial cells had an increased repair response in vitro, as seen by an increased ability of an epithelial monolayer to restore its structural integrity. In conclusion, Nlrp3 shows a tissue-specific role in which leukocyte-associated Nlrp3 is associated with tubular apoptosis, whereas renal-associated Nlrp3 impaired wound healing.